Concentration of N,P, K and yield of red raspberry (Rubus idaeus L.) ‘Autumn bliss’ organic intercropped with lupine (Lupinus mutabilis Sweet.) - Jara-Peña, Enoc (2002)
The present investigation was made with the objective of determining the response of the raspberry ‘Autumn Bliss’ autumn producer to the application of a biofertilizer (vermicompost) intercropped with lupine, under greenhouse conditions in Montecillo, Mexico. In the experiment 5 vermicompost levels were studied (0, 30, 60, 90 and 120 g pot–1) and 2 intercropping levels (with or without lupine) totalling 10 treatments and an additional treatment that consisted of chemical fertilization (N100: P80: K80). As vegetable material cold-treated adventitious buds of raspberry were used for 60 days at 5 °C. Statistically significant differences were found in the levels of vermicompost incorporated to the substrate, and levels of 60 up to 90 g pot–1 favored greater concentrations of in N and K in raspberry; and when the raspberry intercropped with lupino, permited a bigger accumulation of P, indicating a positive interaction between these elements. The biggest yield in weight and in number of fruits was obtained with the application of 90 g pot–1 of vermicompost. However, the biggest yield in weight and in number of fruits was obtained when raspberry intercropped with lupine, with the application of 120 g pot–1 of vermicompost.